Epidemiological Evaluation of Meniscal Ramp Lesions in 3214 Anterior Cruciate Ligament–Injured Knees From the SANTI Study Group Database: A Risk Factor Analysis and Study of Secondary Meniscectomy Rates Following 769 Ramp Repairs. Issue 13 (November 2018) - Sonnery-Cottet, Bertrand; Praz, Cesar; Rosenstiel, Nikolaus; Blakeney, William G.; Ouanezar, Herve; Kandhari, Vikram; Vieira, Thais Dutra; Saithna, Adnan
Background: Ramp lesions are characterized by disruption of the peripheral meniscocapsular attachments of the posterior horn of the medial meniscus. Ramp repair performed at the time of anterior cruciate ligament reconstruction (ACLR) has been shown to improve knee biomechanics. Purpose: The primary objectives of this study were to evaluate the incidence of and risk factors for ramp lesions among a large series of patients undergoing ACLR. Secondary objectives were to determine the reoperation rate for failure of ramp repair, defined by subsequent reoperations for partial medial meniscectomy. Study Design: Case-control study; Level of evidence, 3. Case series; Level of evidence, 4. Methods: All patients underwent transnotch posteromedial compartment evaluation of the knee during ACLR. Ramp repair was performed if a lesion was detected. Potentially important risk factors were analyzed for their association with ramp lesions. A secondary analysis of all patients who underwent ramp repair and had a minimum follow-up of 2 years was undertaken to determine the secondary partial meniscectomy rate for failed ramp repair. Results: The overall incidence of ramp lesions in the study population was 23.9% (769 ramp lesions among 3214 patients). Multivariate analysis demonstrated that the presence of ramp lesions was significantly associated with the following risk factors: male sex, patients aged <30 years, revision ACLR, chronic injuries, preoperative side-to-side laxity >6 mm, and concomitant lateral meniscal tears. The secondary meniscectomy rate was 10.8% at a mean follow-up of 45.6 months (range, 24.2-66.2 months). Patients who underwent ACLR + anterolateral ligament reconstruction had a >2-fold reduction in the risk of reoperation for failure of ramp repair as compared with patients who underwent isolated ACLR (hazard ratio, 0.457; 95% CI, 0.226-0.864; P = .021). Conclusion: There is a high incidence of ramp lesions among patients undergoing ACLR. The identification of important risk factors for ramp lesions should help raise an appropriate index of suspicion and prompt posteromedial compartment evaluation. The overall secondary partial meniscectomy rate after ramp repair is 10.8%. Anterolateral ligament reconstruction appears to confer a protective effect on the ramp repair performed at the time of ACLR and results in a significant reduction in secondary meniscectomy rates.